2013
DOI: 10.1021/jp311741h
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theoretical Study of Graphene on Transition-Metal Surfaces: The Role of Metal d-Band in the Potential-Energy Surface

Abstract: The nature of graphene/substrate interfaces needs to be understood to improve the crystalline quality of graphene films grown with chemical vapor deposition (CVD). We have theoretically investigated the potential-energy surface (PES) of graphene on catalyst transition-metal surfaces. The profile of PES highly depends on the type of underlying metals; the orders of the peak-to-valley (PV) values of PES are Cu < Ni < Co (3d), Pd < Rh < Ru (4d), and Pt < Ir < Os (5d). High PV values were found to be provided by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…The second approach (which is more often used) employs a much smaller supercell with stretched lattice constant of graphene (to match the Ru (0001) lattice). [15][16][17] Previous studies have convincingly shown that although the second approach (the stretched model) neglects the long-range lattice variation (the moiré pattern), it does generate essentially the same electronic properties of the system as those obtained from the first approach, therefore can correctly describe the interaction between graphene and Ru (0001) and are good for further analysis.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The second approach (which is more often used) employs a much smaller supercell with stretched lattice constant of graphene (to match the Ru (0001) lattice). [15][16][17] Previous studies have convincingly shown that although the second approach (the stretched model) neglects the long-range lattice variation (the moiré pattern), it does generate essentially the same electronic properties of the system as those obtained from the first approach, therefore can correctly describe the interaction between graphene and Ru (0001) and are good for further analysis.…”
Section: Resultsmentioning
confidence: 95%
“…Density functional theory (DFT)-based computational modeling is the commonly used theoretical tool to understand physical and chemical properties of Ru (0001)-supported graphene. [15][16][17] In literature, two different types of DFT-based approaches have been used. The first one uses a very large supercell (e.g., 11 × 11 graphene unit cells) 17 to describe the so-called moiré pattern originated from the lattice mismatch between graphene and Ru.…”
Section: Resultsmentioning
confidence: 99%
“… where the appearance of a ring was explained by the nearly vanishing covalent bonding strength between the Ag surface and the h‐BN layer . For graphene, one can argue along the same line since DFT calculations predict an increasing energy separation between late transition metal d‐bands and the Dirac point of graphene, resulting in a reduced interaction with increasing the atomic number within a transition metals row . In case of Ag, which terminates the 4d row, distinct covalent bonding can be excluded, and therefore the covalent bonding strength per area cannot be increased by aligning the lattices along particular directions.…”
Section: Resultsmentioning
confidence: 98%
“…However, the larger the interaction between the graphene layer and the metal surface the larger the risk of inducing defects to the graphene layer during the transfer process. Since the strength of graphene metal interaction decreases within the 3d, 4d, and 5d transition metal rows , Ag‐films may be good candidates as intermediate films.…”
Section: Introductionmentioning
confidence: 99%
“…Both of the asymmetric interfaces presented in Table 1 are between two-dimensional sheets. As a more relevant comparison, we mention the DFT study by Toyoda et al where a peak-to-valley difference in the adhesion energy of about 12 meV/atom for the graphene/ Cu(111) interface 18 was reported. Even though this interface is known to be very weak, this value is much larger than our result.…”
Section: Computational Detailsmentioning
confidence: 99%